Unraveling the nature of spin excitations disentangled from charge contributions in a doped cuprate superconductor - Wenliang Zhang; Cliò Efthimia Agrapidis; Yi Tseng; Teguh Citra Asmara; Eugenio Paris; Vladimir N. Strocov; Enrico Giannini; Satoshi Nishimoto; Krzysztof Wohlfeld; Thorsten Schmitt (npj Quantum Materials, 2022)
Abstract The nature of the spin excitations in superconducting cuprates is a key question toward a unified understanding of the cuprate physics from long-range antiferromagnetism to superconductivity. The intense spin excitations up to the over-doped regime revealed by resonant inelastic X-ray scattering bring new insights as well as questions like how to understand their persistence or their relation to the collective excitations in ordered magnets (magnons). Here, we study the evolution of the spin excitations upon hole-doping the superconducting cuprate Bi2Sr2CaCu2O8+δ by disentangling the spin from the charge excitations in the experimental cross section. We compare our experimental results against density matrix renormalization group calculations for a t-J-like model on a square lattice. Our results unambiguously confirm the persistence of the spin excitations, which are closely connected to the persistence of short-range magnetic correlations up to high doping. This suggests that the spin excitations in hole-doped cuprates are related to magnons—albeit short-ranged.